Analysis of remigrant behavior with the grouped Cox model - Beatrix Brecht; Leo Brecht (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The focus of this article is the application of the grouped Cox model to the investigation of influence factors of the inclination of guest workers in the Federal Republic of Germany to remigrate. The model on which this is based takes into consideration both the appearance of censored observations and the discrete-time raised length of stay, which the application of a continuous time sojourn model does not permit. The estimations were made with the program PRODISA (Program for Discrete Survival Analysis), which was developed in the context of this project. The Socio-Economic Panel of the DIW, Berlin, serves as the basis of the data.
Keywords: 330; grouped Cox Model; time-discrete sojourn; covariate design; PRODISA; remigrant behavior; guest worker; Rückwanderung; Arbeitsmigranten; Schätztheorie; Deutschland